Myotoxic and hemorrhagic effects of fractions obtained from the venom of lionfish (pterois volitans) in mice and identification of potentially toxic components - Díaz Oreiro, Cecilia (2020)
Poster publicado en revista del congreso: 20th World Congress of the International Society on Toxinology